CBMS-12 PENTAMIDINE; TRANSLATIONAL RESEARCH FOR A NEW CHEMOTHERAPY TARGETING ON GLIOMA CELLS AND GLIOMA STEM CELLS USING DRUG REPOSITIONING - Tamai, Sho (Neurooncol Adv, 2019)
INTRODUCTION: Glioblastoma (GBM) is primary malignant brain tumor with poor prognosis. Despite aggressive chemoradiotherapies, GBM has resistance and finally relapses. Recently, it is revealed that glioma stem cells (GSCs) are forming tumors and induce the recurrence. However, there is no effective therapy for GSCs. Herein, we newly identified pentamidine, an antiprotozoal drug, is effective for not only glioma cells but also GSCs by using drug repositioning approach. METHOD: We used two glioma cell lines, A172 and T98, and patient-derived glioma stem cell lines KGS01, KGS07 which were established at Kanazawa University. We investigated proliferation ability, stemness and intracellular signal change by proliferation assay, sphere forming assay and western blotting, respectively. RESULT Proliferation ability was prohibited by pentamidine in both glioma cell lines and GSC lines. The half maximal inhibitory concentrations were 5–10 μM in glioma cell lines and 1–5 μM in GSC lines. Sphere forming assay revealed that size and number of spheres were reduced in both GSC lines, depending on concentration of pentamidine. In all cell lines, phosphorylation of extracellular signal-related kinase (ERK) and signal transducer and activator of transcription 3 (STAT3) were suppressed by pentamidine. DISCUSSION: Pentamidine is known as the therapeutic drug for pneumocystis jirovecii. In this study, pentamidine suppressed proliferation activity in all cell lines, and stemness in both GSCs. Previous papers revealed pentamidine had anti-tumor effects for some types of tumor cell lines, however, therapeutic effect for tumor stem cells have never been mentioned. CONCLUSION: These results suggest that pentamidine would be therapeutic drug for not only glioma cells but also GSCs by suppressing phosphorylation of ERK and STAT3.